FEATURES OF THE METHODOLOGICAL APPROACH TO THE STUDY OF THE DYNAMICS OF THE GAS DISTRIBUTION MECHANISM OF TRANSPORT POWER INSTALLATIONS - Логвіненко, Олександр (SWorldJournal, 2024)
The article discusses the topical issue of the need to conduct a dynamic study of the gas distribution mechanism of transport power plants, the purpose of which is to calculate the actual valve movement taking into account inertial, elastic-dissipative p